Pengaruh Kepercayaan, Transparansi dan Akuntabilitas terhadap Minat dan Keputusan Muzakki Menyalurkan Zakat, di (LAZISNU) Kabupaten Banyuwangi - muhammad kanzul fikri; ahmad ainun najib (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
The purpose of this study was to determine the effect of trust, transparency and accountability on muzakki's interests and decisions. Subjects in this study were muzakki in Banyuwangi district which were channeled through LAZISNU with a total of 110 respondents. This type of research uses quantitative methods with the type of experiment in the form of explanatory research. The results showed that there was a significant influence between trust in muzakki interest with tcount Ëƒttable (4.390> 1.659) and a significance value of 0.00 <0.05. There is a significant influence between transparency on muzakki interest with tcount Ëƒttabel (2.763> 1.659) and a significance value of 0.007 <0.05 and there is a significant effect between accountability on muzakki interest with tcount Ëƒttabel (3.674> 1.659) and a significance value of 0.00 <0.05, and there is a significant influence between accountability on muzakki decisions with tcount Ëƒttable (2.481> 1.659) and a significance value of 0.015 <0.05 and there is a significant influence between muzakki interest on muzakki decisions with tcount Ëƒ t table (3.905> 1.659) and a significance value of 0.00 <0.05, but the insignificant effect between trust in muzakki decisions with t count <t table (1.615 <1.659) and a significance value of 0.109> 0.05 and transparency towards decisions muzakki with tcount <ttable (1.208 <1.659) and a significance value of 0.230> 0.05.